2014
DOI: 10.1016/j.molcel.2014.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-Coupled Nucleotide Excision Repair Factors Promote R-Loop-Induced Genome Instability

Abstract: Summary R-loops, consisting of an RNA-DNA hybrid and displaced single-stranded DNA, are physiological structures that regulate various cellular processes occurring on chromatin. Intriguingly, changes in R-loop dynamics have also been associated with DNA damage accumulation and genome instability, however the mechanisms underlying R-loop induced DNA damage remain unknown. Here we demonstrate in human cells that R-loops induced by the absence of diverse RNA processing factors, including the RNA/DNA helicases Aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
525
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 498 publications
(550 citation statements)
references
References 45 publications
24
525
1
Order By: Relevance
“…We have shown that association of ( pT371)TRF1 with APBs is sensitive to RNaseH1 in the presence of camptothecin, an inhibitor of topoisomerase I, an enzyme known to prevent the formation of RNA-DNA hybrids and to resolve conflicts between transcription and replication (Hamperl and Cimprich, 2014;Tuduri et al, 2009). RNA-DNA hybrids can be processed into DNA double-strand breaks (DSBs) (Sollier et al, 2014), and recently, it has been reported that DNA DSBs at ALT telomeres induce telomere clustering, APB formation as well as other homologousrecombination-based ALT activities (Cho et al, 2014). Perhaps, telomeric RNA-DNA hybrids arising from transcription and replication collision might be a natural source of DNA damage that triggers ALT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that association of ( pT371)TRF1 with APBs is sensitive to RNaseH1 in the presence of camptothecin, an inhibitor of topoisomerase I, an enzyme known to prevent the formation of RNA-DNA hybrids and to resolve conflicts between transcription and replication (Hamperl and Cimprich, 2014;Tuduri et al, 2009). RNA-DNA hybrids can be processed into DNA double-strand breaks (DSBs) (Sollier et al, 2014), and recently, it has been reported that DNA DSBs at ALT telomeres induce telomere clustering, APB formation as well as other homologousrecombination-based ALT activities (Cho et al, 2014). Perhaps, telomeric RNA-DNA hybrids arising from transcription and replication collision might be a natural source of DNA damage that triggers ALT.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-DNA hybrids, also known as R loops, can be processed to give rise to DNA doublestrand breaks (Hamperl and Cimprich, 2014;Sollier et al, 2014). To investigate if RNA-DNA hybrids might regulate ( pT371)TRF1 recruitment to APBs, we generated U2OS cell lines stably expressing the vector alone or Myc-tagged RNaseH1 (Fig.…”
Section: Rna-dna Hybrids Modulate the Association Of (Pt371)trf1 Withmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, R-loops have long been associated with replicative stress and genome instability, whereas more recent work indicates that RNA-DNA hybrids can also promote DNA repair by mechanisms that remain to be elucidated (23)(24)(25)(26)(27). Considering the importance of RNA-DNA structures in DNA repair and genome instability, we proceeded to examine whether Polθ-helicase unwinds RNA-DNA duplexes with similar efficiency.…”
Section: Polθ-helicase Unwinds Dna In An Atp and Datp Dependent Mannermentioning
confidence: 99%
“…Thus, RNA-DNA helicases are required for the replication of highly transcribed regions (Boubakri et al 2010), and R-loop accumulation impairs replication fork progression from bacteria to human cell lines (Wellinger et al 2006;Tuduri et al 2009;Gan et al 2011;CastellanoPozo et al 2012;Hamperl et al 2017). Alternatively, R loops may generate genomic instability if the displaced ssDNA is recognized and processed by flap endonucleases (Sollier et al 2014). Despite reports showing that R loops alter replication, causing genome instability, the mechanism is still unclear.…”
mentioning
confidence: 99%